Sosiologi Pilihan Studi Lanjut Siswa Madrasah Aliyah: Studi tentang Aspirasi Keagamaan, Kapital Keluarga, dan Imajinasi Masa Depan - Najwa Zakiyatiz Zulfa; Muh. Hanif (Al-Kindi, 2026)
This article examines the sociology of Madrasah Aliyah students' choices of further study by highlighting the influence of religious aspirations, family capital, and future imagination. The decision to continue education is not only based on academic considerations but is also influenced by social, cultural, and religious factors. This research uses an educational aspiration study approach with data collection techniques through observation, interviews, and documentation. The results show that parents and teachers, peers, as well as religious figures play a significant role in shaping students' decisions regarding the college and study program they choose. Families with higher economic capital and educational attainment tend to provide broader access to information, thus providing stronger guidance in the decision-making process. On the other hand, religious aspirations encourage students to choose fields of study that are considered aligned with Islamic values. The choice of further study is also influenced by students' imaginations about the future, such as the desire to become a teacher, lecturer, or work in the formal sector. This article confirms that Madrasah Aliyah students' choices of further study are the result of the interaction between religious values, family capital, the prestige of the study program, and future orientation. These findings are important for the development of career guidance services in Islamic educational institutions.